Composite light evaporator for desalting light evaporation water body and preparation method of composite light evaporator

By combining ice powder seed glue with carbon nanotubes and copper acetate, a high-efficiency photoevaporator is prepared, which solves the problems of solar energy dispersion and natural photothermal efficiency, realizes high-efficiency photothermal conversion and stable water evaporation, and has good salt resistance Sexual and biocompatible.

CN119191430AActive Publication Date: 2024-12-27YANCHENG INST OF TECH

Patent Information

Application Number
CN202411571909.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2024-12-27
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

In the existing photoevaporation water desalination technology, solar energy dispersion and natural photothermal efficiency are low, which cannot meet the needs of high-efficiency photothermal evaporation water. The preparation process is complex and the conditions are strict.

Method used

A composite photoevaporator is adopted to form an optical evaporator with high light absorption and hydrophobic surface by mixing ice powder seed glue with carbon nanotubes, adding copper acetate solution, and freeze-drying and carbonizing treatment. The carbon nanotubes are used. The capillary effect and the local surface plasmon resonance effect of the Cu layer improve the photothermal conversion efficiency.

Benefits of technology

It achieves efficient photothermal conversion and moisture evaporation, with a light absorption rate of 98%, a stable evaporation rate, a long service life, and good salt resistance and biocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191430A_ABST
    Figure CN119191430A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of light evaporation water desalination, and particularly relates to a composite light evaporator for light evaporation water desalination and a preparation method thereof.Carbon nanotubes with excellent light absorption and water delivery capacity are dispersed in a biomass material, meanwhile, a layer of copper acetate is sprayed on the upper surface of the biomass material with the carbon nanotubes, and the composite light evaporator is prepared. And the copper particles are formed after carbonization. According to the prepared optical evaporator, the metal, the carbon nano tube and the biomass material are combined, and the optical evaporator has different hydrophilic and hydrophobic properties and high salt resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of light evaporation water desalination, and in particular relates to a composite light evaporator for light evaporation water desalination and a preparation method thereof. Background Art

[0002] Due to the rapid population growth and increasing environmental pollution, the water crisis has become a well-known and urgent problem. Therefore, a variety of water desalination technologies have been developed to alleviate this problem. Among them, the use of solar energy to obtain freshwater resources from seawater is one of the technologies with high potential for development. As we all know, solar energy has the advantages of sustainability, environmental friendliness and cheap sources, providing a free heat source for water evaporation. However, due to the dispersion of solar energy, the low efficiency of natural photothermal energy, and the low light absorption rate of water bodies, it is impossible to meet the needs of efficient photothermal evaporation of water bodies. To alleviate these problems, it is an effective strategy to use efficient light-absorbing interface materials to effectively convert light energy into heat energy during the photothermal conversion process and improve the local photothermal evaporation efficiency.

[0003] With the development of science and technology, more and more biomass materials have been prepared and have high application potential. For example, Wang et al. (Chemical Engineering Journal, 2023. DOI: 10.1016 / j.cej.2023.142265.) reported a preparation method of a photoevaporator based on a loofah sponge, Chen et al. (Small, 2023, 19(48): n / an / a. DOI: 10.1002 / smll.202303908.) demonstrated a cotton-based photoevaporator made by Pickering emulsion polymerization, and Zhang et al. (Nano Energy, 2020, 78. DOI: 10.1016 / j.nanoen.2020.105322.) used a p-toluenesulfonic acid-assisted hydrothermal treatment of wood photoevaporator for photoevaporation. However, these preparation processes are relatively complex and the preparation conditions are also relatively harsh. Summary of the invention

[0004] The present invention mainly provides a composite optical evaporator with different hydrophilicity and strong salt resistance for desalination of water by optical evaporation and a preparation method thereof. The specific scheme is as follows:

[0005] A preparation method of a composite photoevaporator for photoevaporation water desalination comprises the following steps: adding carbon nanotubes to biogel and mixing them evenly to obtain hydrogel by ice template method; then freeze-drying to obtain an aerogel base layer; spraying a layer of copper acetate solution on the upper surface of the base layer, and then performing secondary freeze-drying; and finally obtaining the composite photoevaporator by carbonization treatment.

[0006] Furthermore, the biogel is made of ice powder seed gel; and the carbon nanotube is made of multi-walled carbon nanotube.

[0007] Furthermore, the concentration of the carbon nanotubes in the biogel is 12-35 g / L; and the copper acetate solution is a saturated solution.

[0008] Furthermore, the mass ratio of copper acetate to biogel in the copper acetate solution is 1:60-125.

[0009] Furthermore, the preparation method of the ice powder seed glue is: soak the ice powder seeds in water at a mass ratio of 1:5-10 for 5-20 minutes; then repeatedly kneading at 2-8°C until the solution becomes colloid and flows slowly, to obtain a light yellow transparent paste of ice powder seed glue.

[0010] Further, the following steps are included:

[0011] a. Rapidly add carbon nanotubes to the biogel, stir thoroughly to make them evenly dispersed, let it stand and solidify, freeze until the water in the biogel freezes into ice to obtain a hydrogel; freeze-dry the hydrogel to obtain an aerogel base layer;

[0012] b. Prepare a copper acetate solution and then spray it onto the aerogel substrate. After spraying, freeze-dry it again, then heat it to 500-650°C and carbonize it for 1-2 hours to obtain a composite optical evaporator.

[0013] Furthermore, the freezing in step a is performed at a temperature below -18°C for 4 to 18 hours; the freeze-drying temperature in step a is -30 to -70°C, and the vacuum degree is not higher than 2Pa.

[0014] Furthermore, the heating rate in step b is 1-3°C / min.

[0015] A composite optical evaporator for optical evaporation water desalination prepared by the above preparation method comprises a hydrophilic base layer and a hydrophobic metal surface layer covering the surface of the base layer.

[0016] Furthermore, it absorbs light of all wavelengths, and the light absorption rate is not less than 95%.

[0017] By adopting the above scheme, the method of the present invention has the following advantages:

[0018] 1. The ice powder seeds of the present invention are a common renewable biomass energy source in nature. The gel formed by rubbing has good biocompatibility and an easily adjustable water transmission channel. Compared with non-biomass gel, it also has the characteristics of being renewable and non-toxic. At the same time, carbon nanotubes can provide good light absorption and capillary effect, providing a good channel for water transmission.

[0019] 2. The copper acetate sprayed on the surface of the optical evaporator of the present invention forms a Cu layer after high-temperature carbonization. Cu exhibits adjustable light absorption due to its local surface plasmon resonance effect. When Cu is irradiated by sunlight, the energy is equivalent to bandgap photons, which will generate electron-hole pairs. The excited electrons release energy and return to their ground state, while converting the irradiation energy into heat energy, reducing heat loss and promoting heat management. Cu, which has high thermal conductivity and can be used as an ideal photothermal conversion material, works synergistically with carbon nanotubes to improve the photothermal conversion efficiency and water evaporation rate.

[0020] 3. The hydrophobicity of the copper metal layer on the surface of the composite evaporator of the present invention prevents the interference of excessive wetting of water, ensuring the dryness of the photothermal conversion interface. At the same time, the biomass matrix with carbon nanotubes added is hydrophilic, and the two work together to ensure that there is sufficient water to reach the photothermal conversion interface during the evaporation process, with asymmetric wettability, maintaining stable heat exchange at the junction of the biomass and the metal layer, and reducing heat loss.

[0021] 4. The capillary effect of the carbon nanotubes in the base layer of the composite evaporator of the present invention provides a transmission channel for salt ions during the evaporation process. The local salt concentration at the water-air interface increases, but the salt ions can diffuse back to the bulk water by the capillary effect, thereby inhibiting the crystallization of salt on the surface of the evaporator. At the same time, the biomass material, as a poor conductor of heat, prevents the heat from being lost downward, achieving the effect of heat aggregation.

[0022] 5. The light absorption rate of the optical evaporator of the composite evaporator of the present invention is as high as 98%, showing full-band absorption of sunlight, the evaporation rate remains stable, and has a long service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope image of the composite optical evaporator synthesized in Example 1.

[0024] Figure 2 This is a scanning electron microscope image of the aerogel base layer synthesized in step 2 of Example 1.

[0025] Figure 3 This is a scanning electron microscope image of the composite optical evaporator synthesized in step 3 of Example 1.

[0026] Figure 4 This is a transmission electron microscope image of the composite photoevaporator synthesized in Example 1.

[0027] Figure 5 This is a transmission electron microscope image of the aerogel base layer synthesized in step 2 of Example 1.

[0028] Figure 6 This is a transmission electron microscope image of the composite photoevaporator synthesized in step 3 of Example 1.

[0029] Figure 7 This is a scanning electron microscope image of the composite optical evaporator synthesized in Comparative Example 7.

[0030] Figure 8 This is a scanning electron microscope image of the composite optical evaporator synthesized in Comparative Example 8.

[0031] Fig. 9 It is the light absorption curve of the composite optical evaporator synthesized in Example 1 and Comparative Examples 9 to 11.

[0032] Fig.10 This is a thermal imaging temperature rise diagram of the composite optical evaporator synthesized in Example 1.

[0033] Fig.11 This is a pure water evaporation mass loss-time curve of the composite optical evaporator synthesized in Example 1.

[0034] Fig.12 This is a comparison chart of the evaporation rates of the composite optical evaporator synthesized in Example 1 at different brine concentrations.

[0035] Fig.13 This is a continuous cycle evaporation rate diagram of the composite optical evaporator synthesized in Example 1.

[0036] Fig.14 Pure water evaporation time-temperature curves of the composite optical evaporator synthesized in Example 1 and Comparative Examples 1 to 3.

[0037] Fig.15 Pure water evaporation time-evaporation rate curve of the composite optical evaporator synthesized in Example 1 and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Embodiment 1:

[0040] (1) Take 10g of ice powder seeds and soak them in 80mL of deionized water at 2-8°C for 8min, then knead them repeatedly to produce gelatin until the solution becomes viscous, thereby obtaining light yellow transparent paste of ice powder seeds.

[0041] (2) 1.5 g of carbon nanotubes were quickly added to the above-mentioned ice powder seed gel, and the mixture was stirred thoroughly to make it evenly dispersed. After standing for solidification, the mixture was placed in a -18°C refrigerator for 12 h to obtain a hydrogel. After completion, the mixture was freeze-dried at -50°C and 1 Pa to obtain an aerogel.

[0042] (3) 1 g of copper acetate was dissolved in 80 mL of deionized water to prepare a saturated solution, which was sprayed on the upper surface of the aerogel; after the upper layer was completely covered by the solution, freeze-drying was performed again, and finally the temperature was increased to 600 °C at 1.5 °C / min and kept constant for 90 min to obtain a composite optical evaporator (Cu@CNTs-IP).

[0043] Depend on Figure 1 and Figure 3 From the scanning electron microscope photograph, it can be seen that the sample has a lamellar structure, and the lamellar surface is loaded with uniform copper particles formed after carbonization. Figure 2 It can be seen that the carbon nanotubes are evenly distributed on the layer structure.

[0044] Figure 4 and Figure 6 The transmission electron microscope photograph shows that the copper particles are uniform in size and are evenly distributed with the carbon nanotubes. Figure 5 It can be seen that the carbon nanotubes have an obvious hollow structure, which indicates that the preparation method of the present invention will not destroy the morphology of the carbon nanotubes and can support the typical capillary effect.

[0045] Depend on Fig. 9 It can be seen from the light absorption curve that the light evaporator prepared by the preparation method of the present invention can improve the light absorption rate while retaining the full-band absorption property of sunlight, and the light absorption rate can reach an extremely high 98%. Fig.10 The thermal imaging temperature rise diagram shows that the light evaporator of the present invention can quickly heat up to 88.4° C. within 180 seconds under 1 sun, which indicates that it has good light conversion potential.

[0046] Embodiment 2:

[0047] (1) Take 10g of ice powder seeds and soak them in 70mL of deionized water at 2-8°C for 8min, then knead them repeatedly to produce gelatin until the solution becomes viscous, thereby obtaining light yellow transparent paste of ice powder seeds.

[0048] (2) 1.5 g of carbon nanotubes were quickly added to the above-mentioned ice powder seed gel, and the mixture was stirred thoroughly to make it evenly dispersed. After standing for solidification, the mixture was placed in a -18°C refrigerator for 12 h to obtain a hydrogel. After completion, the mixture was freeze-dried at -50°C and 1 Pa to obtain an aerogel.

[0049] (3) 0.8 g of copper acetate was dissolved in deionized water to prepare a saturated solution, which was sprayed on the upper surface of the aerogel; after the upper layer was completely covered by the solution, freeze-drying was performed again, and finally the temperature was increased to 600° C. at 1.5° C. / min and kept constant for 90 minutes to obtain a composite optical evaporator.

[0050] Embodiment 3:

[0051] (1) Take 10g of ice powder seeds and soak them in 80mL of deionized water at 2-8°C for 8min, then knead them repeatedly to produce gelatin until the solution becomes viscous, thereby obtaining light yellow transparent paste of ice powder seeds.

[0052] (2) 1.5 g of carbon nanotubes were quickly added to the above-mentioned ice powder seed gel, and the mixture was stirred thoroughly to make it evenly dispersed. After standing for solidification, the mixture was placed in a -18°C refrigerator for 6 h to obtain a hydrogel. After completion, the mixture was freeze-dried at -50°C and 1 Pa to obtain an aerogel.

[0053] (3) 1 g of copper acetate was dissolved in 80 mL of deionized water to prepare a saturated solution, which was sprayed on the upper surface of the aerogel; after the upper layer was completely covered by the solution, freeze-drying was performed again, and finally the temperature was increased to 550° C. at 1.5° C. / min and kept constant for 90 min to obtain a composite optical evaporator.

[0054] Embodiment 4:

[0055] (1) Take 10 g of ice powder seeds and soak them in 100 mL of deionized water at 2-8°C for 8 min, then repeatedly knead them to produce a colloid until the solution becomes viscous, thereby obtaining a light yellow transparent paste of ice powder seeds.

[0056] (2) 1.5 g of carbon nanotubes were quickly added to the above-mentioned ice powder seed gel, and the mixture was stirred thoroughly to make it evenly dispersed. After standing for solidification, the mixture was placed in a -18°C refrigerator for 8 h to obtain a hydrogel. After completion, the mixture was freeze-dried at -50°C and 1 Pa to obtain an aerogel.

[0057] (3) 1 g of copper acetate was dissolved in 80 mL of deionized water to prepare a saturated solution, which was sprayed on the upper surface of the aerogel; after the upper layer was completely covered by the solution, freeze-drying was performed again, and finally the temperature was increased to 650° C. at 1.5° C. / min and kept constant for 90 min to obtain a composite optical evaporator.

[0058] Comparative Example 1:

[0059] (1) Take 10g of ice powder seeds and soak them in 50mL of deionized water at 2-8°C for 8min, then knead them repeatedly to produce gelatin until the solution becomes viscous, thereby obtaining yellow transparent paste of ice powder seeds.

[0060] (2) 1.5 g of carbon nanotubes were quickly added to the above-mentioned ice powder seed gel, and the mixture was stirred thoroughly to make it evenly dispersed. After standing for solidification, the mixture was placed in a -18°C refrigerator for 4 h to obtain a hydrogel. After completion, the mixture was freeze-dried at -50°C and 1 Pa to obtain an aerogel.

[0061] (3) 0.1 g of copper acetate was dissolved in 80 mL of deionized water and sprayed on the upper surface of the aerogel; after the upper layer was completely covered by the solution, freeze-drying was performed again, and finally the temperature was increased to 450° C. at 1.5° C. / min and kept constant for 90 min to obtain a composite optical evaporator.

[0062] The product obtained had an unclear local plasma effect due to the short freezing time, low concentration of the sprayed copper acetate solution, and too little mass. The photothermal conversion capacity was not sufficiently improved, and the carbonization temperature was low, resulting in the collapse of the photoevaporator during the evaporation process.

[0063] Comparative Example 2:

[0064] (1) Take 10g of ice powder seeds and soak them in 70mL of deionized water at 2-8°C for 8min, then knead them repeatedly to produce gelatin until the solution becomes viscous, thereby obtaining light yellow transparent paste of ice powder seeds.

[0065] (2) 1.5 g of carbon nanotubes were quickly added to the above-mentioned ice powder seed gel, and the mixture was stirred thoroughly to make it evenly dispersed. After it was allowed to stand and solidify, it was placed in a -18°C refrigerator for 5 h to obtain a hydrogel. After completion, it was freeze-dried at -50°C and 1 Pa to obtain an aerogel.

[0066] (3) 0.6 g of copper acetate was dissolved in 80 mL of deionized water and sprayed on the upper surface of the aerogel; after the upper layer was completely covered by the solution, freeze-drying was performed again, and finally the temperature was increased to 600° C. at 1.5° C. / min and kept constant for 90 min to obtain a composite optical evaporator.

[0067] The obtained product has a loose structure of the photoevaporator due to the relatively short freezing time and the low concentration of the sprayed copper acetate solution, resulting in a low photothermal conversion efficiency.

[0068] Comparative Example 3:

[0069] (1) Take 10 g of ice powder seeds and soak them in 100 mL of deionized water at 2-8°C for 8 min, then repeatedly knead them to produce a colloid until the solution becomes viscous, thereby obtaining a light yellow transparent paste of ice powder seeds.

[0070] (2) 1.5 g of carbon nanotubes were quickly added to the above-mentioned ice powder seed gel, and the mixture was stirred thoroughly to make it evenly dispersed. After standing for solidification, the mixture was placed in a -18°C refrigerator for 8 h to obtain a hydrogel. After completion, the mixture was freeze-dried at -50°C and 1 Pa to obtain an aerogel.

[0071] (3) 0.8 g of copper acetate was dissolved in 80 mL of deionized water and sprayed on the upper surface of the aerogel; after the upper layer was completely covered by the solution, freeze-drying was performed again, and finally the temperature was increased to 700° C. at 1.5° C. / min and kept constant for 90 min to obtain a composite optical evaporator.

[0072] The obtained product has a gray surface after carbonization of the photoevaporator due to excessive deionized water added to the copper acetate solution, unsaturated spraying concentration and high carbonization temperature, and the edge of the photoevaporator curls, reducing its structural toughness, and causing its absorbance to decrease and the photothermal conversion efficiency to decrease.

[0073] Comparative Example 4:

[0074] (1) Take 10g of ice powder seeds and soak them in 80mL of deionized water at 2-8°C for 3min, then knead them repeatedly to produce gelatin until the solution becomes viscous, thereby obtaining light yellow transparent paste of ice powder seeds.

[0075] (2) 0.8 g of carbon nanotubes was quickly added to the above-mentioned ice powder seed gel, and the mixture was stirred thoroughly to make it evenly dispersed. After it was allowed to stand and solidify, it was placed in a -18°C refrigerator for 12 hours to obtain a hydrogel. After completion, it was freeze-dried at -50°C and 1 Pa to obtain an aerogel.

[0076] (3) Dissolve 1 g of copper acetate in 80 mL of deionized water to prepare a saturated solution, and spray the solution on the upper surface of the aerogel; after the upper layer is completely covered by the solution, freeze-dry the solution again, and finally heat the solution to 600° C. at 1.5° C. / min and keep the temperature constant for 90 min to obtain a composite optical evaporator.

[0077] The soaking time is too short, resulting in the incomplete diffusion of effective cross-linking components into the water body, reducing the concentration of ice powder seed glue and poor structural strength of the optical evaporator.

[0078] Comparative Example 5:

[0079] (1) Take 10g of ice powder seeds and soak them in 80mL of deionized water at 15℃ for 8min, then knead them repeatedly to produce gelatin until the solution becomes viscous, thereby obtaining light yellow transparent paste of ice powder seeds.

[0080] (2) 0.8 g of carbon nanotubes was quickly added to the above-mentioned ice powder seed gel, and the mixture was stirred thoroughly to make it evenly dispersed. After it was allowed to stand and solidify, it was placed in a -18°C refrigerator for 12 hours to obtain a hydrogel. After completion, it was freeze-dried at -50°C and 1 Pa to obtain an aerogel.

[0081] (3) Dissolve 1 g of copper acetate in 80 mL of deionized water to prepare a saturated solution, and spray the solution on the upper surface of the aerogel; after the upper layer is completely covered by the solution, freeze-dry the solution again, and finally heat the solution to 600° C. at 1.5° C. / min and keep the temperature constant for 90 min to obtain a composite optical evaporator.

[0082] The kneading temperature of the ice powder seeds is too high, which causes the effective ingredients in the ice powder to be destroyed, reduces the self-polymerization rate, and the finished product morphology of the composite light evaporator is poor.

[0083] Comparative Example 6:

[0084] (1) Take 10g of ice powder seeds and soak them in 80mL of deionized water at 2-8°C for 8min, then knead them repeatedly to produce gelatin until the solution becomes viscous, thereby obtaining light yellow transparent paste of ice powder seeds.

[0085] (2) 0.8 g of carbon nanotubes was quickly added to the above-mentioned ice powder seed gel, and the mixture was stirred thoroughly to make it evenly dispersed. After it was allowed to stand and solidify, it was placed in a -18°C refrigerator for 12 hours to obtain a hydrogel. After completion, it was freeze-dried at -50°C and 1 Pa to obtain an aerogel.

[0086] (3) Dissolve 1 g of copper acetate in 80 mL of deionized water to prepare a saturated solution, and spray the solution on the upper surface of the aerogel; after the upper layer is completely covered by the solution, freeze-dry the solution again, and finally heat the solution to 600° C. at 1.5° C. / min and keep the temperature constant for 90 min to obtain a composite optical evaporator.

[0087] The mass of carbon nanotubes is too small, the absorbance and capillary effect of the photoevaporator are reduced, and the photothermal conversion efficiency is not high.

[0088] Comparative Example 7:

[0089] (1) Take 10g of ice powder seeds and soak them in 80mL of deionized water at 2-8°C for 8min, then knead them repeatedly to produce gelatin until the solution becomes viscous, thereby obtaining light yellow transparent paste of ice powder seeds.

[0090] (2) Quickly add 2 g of carbon nanotubes to the above ice powder seed gel, stir thoroughly to make it evenly dispersed, let it stand until it solidifies and then put it in a -18°C refrigerator for 12 hours to obtain hydrogel; after completion, freeze-dry it at -50°C and 1 Pa to obtain aerogel.

[0091] (3) Dissolve 1 g of copper acetate in 80 mL of deionized water to prepare a saturated solution, and spray the solution on the upper surface of the aerogel; after the upper layer is completely covered by the solution, freeze-dry the solution again, and finally heat the solution to 600° C. at 1.5° C. / min and keep the temperature constant for 90 min to obtain a composite optical evaporator.

[0092] Depend on Figure 7 It can be seen that the excessive mass of carbon nanotubes causes agglomeration, which leads to blockage of water transmission channels and reduces the water transmission rate.

[0093] Comparative Example 8:

[0094] (1) Take 10g of ice powder seeds and soak them in 80mL of deionized water at 2-8°C for 8min, then knead them repeatedly to produce gelatin until the solution becomes viscous, thereby obtaining light yellow transparent paste of ice powder seeds.

[0095] (2) 1.5 g of carbon nanotubes were quickly added to the above-mentioned ice powder seed gel, and the mixture was stirred thoroughly to make it evenly dispersed. After standing for solidification, the mixture was placed in a -18°C refrigerator for 12 h to obtain a hydrogel. After completion, the mixture was freeze-dried at -50°C and 1 Pa to obtain an aerogel.

[0096] (3) 1.5 g of copper acetate was dissolved in 120 mL of deionized water to prepare a saturated solution, which was sprayed on the upper surface of the aerogel; after the upper layer was completely covered by the solution, freeze-drying was performed again, and finally the temperature was increased to 600° C. at 1.5° C. / min and kept constant for 90 min to obtain a composite optical evaporator.

[0097] Depend on Figure 8 It can be seen that the excessive mass of copper acetate results in excessive Cu particles, which accumulate and destroy the moisture transmission channel of the material, and also cause waste of reagents.

[0098] Comparative Example 9:

[0099] (1) Take 10g of ice powder seeds and soak them in 80mL of deionized water at 2-8°C for 8min, then knead them repeatedly to produce gelatin until the solution becomes viscous, thereby obtaining light yellow transparent paste of ice powder seeds.

[0100] (2) After the ice powder seed gel is allowed to solidify, it is placed in a -18°C refrigerator for 12 hours to obtain a hydrogel; after completion, it is freeze-dried at -50°C and 1 Pa to obtain an aerogel (IP).

[0101] Comparative Example 10:

[0102] (1) Take 10g of ice powder seeds and soak them in 80mL of deionized water at 2-8°C for 8min, then knead them repeatedly to produce gelatin until the solution becomes viscous, thereby obtaining light yellow transparent paste of ice powder seeds.

[0103] (2) 1.5 g of carbon nanotubes were quickly added to the above ice powder seed gel, and the mixture was stirred thoroughly to make it evenly dispersed. After it was allowed to stand and solidify, it was placed in a -18°C refrigerator for 12 h to obtain a hydrogel. After completion, it was freeze-dried at -50°C and 1 Pa to obtain an aerogel (CNTs-IP).

[0104] Comparative Example 11:

[0105] (1) Take 10g of ice powder seeds and soak them in 80mL of deionized water at 2-8°C for 8min, then knead them repeatedly to produce gelatin until the solution becomes viscous, thereby obtaining light yellow transparent paste of ice powder seeds.

[0106] (2) After the ice powder seed gel is allowed to solidify, it is placed in a -18°C refrigerator for 12 hours to obtain a hydrogel; after completion, it is freeze-dried at -50°C and 1 Pa to obtain an aerogel.

[0107] (3) 1 g of copper acetate was dissolved in 80 mL of deionized water to prepare a saturated solution, which was sprayed on the upper surface of the aerogel; after the upper layer was completely covered by the solution, freeze-drying was performed again, and finally the temperature was increased to 600°C at 1.5°C / min and kept constant for 90 minutes to obtain a composite optical evaporator (Cu-IP).

[0108] Example sample test:

[0109] The photothermal conversion experiment was carried out at an ambient temperature of 25°C and a humidity of 45%. The prepared composite photoevaporator was placed on a water surface. A xenon lamp (PLS-SXE 300 / 300UV) was used to irradiate the sample to simulate the irradiation of sunlight. An analytical balance (ME 204E, Mettler-Toledo, USA) was used to record the mass loss of water during the evaporation process, and an infrared (IR) thermal imager (~0.4°C measurement error) was used to record the temperature of different samples. The water samples were deionized water and 0wt%~20wt% NaCl solution, respectively.

[0110] Depend on Fig.11 It can be seen from the pure water evaporation mass loss-time curve of the composite light evaporator synthesized in Example 1 that with the increase of light intensity, the evaporation capacity of Example 1 first increases and then decreases, proving that when the light evaporator is irradiated with higher sunlight intensity, the high temperature generated at its photothermal interface is conducive to the evaporation of liquid water, but at the same time, the heat conduction, heat radiation and heat convection losses on its surface will also increase.

[0111] Fig.12 This is a comparison chart of the evaporation rates of the composite optical evaporator synthesized in Example 1 under different salt water concentrations. As the salt water concentration increases, the water evaporation rate of the optical evaporator increases, which proves that it has good salt resistance. The composite optical evaporator of the present invention has certain practical application capabilities.

[0112] Fig.13This is a continuous cycle evaporation rate diagram of the composite optical evaporator synthesized in Example 1. Under natural light for five consecutive days, a photothermal evaporation experiment was carried out using a 3.5wt% sodium chloride solution. It can be seen from the figure that during the five consecutive days of evaporation, the evaporation rate remained stable, proving that the composite optical evaporator of the present invention has a long service life.

[0113] Fig.14 The pure water evaporation time-temperature curve of the composite light evaporator synthesized in Example 1 and Comparative Examples 1 to 3 shows that during the evaporation process, the surface temperature of Example 1 is always higher than that of Comparative Examples 1, 2 and 3, which proves that Example 1 has better absorbance and excellent light-to-heat conversion capability.

[0114] Fig.15 The evaporation rate curve of pure water evaporation of the composite optical evaporator synthesized in Example 1 and Comparative Examples 1 to 3 shows that during the evaporation process, the water evaporation rate of Example 1 is higher than that of Comparative Examples 1, 2 and 3, which proves that it has a strong water transmission capacity and a high photothermal conversion efficiency.

[0115] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a composite optical evaporator for optical evaporation water desalination, characterized in that: The method comprises the following steps: adding carbon nanotubes to biogel and mixing them evenly, obtaining hydrogel by ice template method; then freeze-drying to obtain aerogel base layer; spraying a layer of copper acetate solution on the upper surface of the base layer, and then performing secondary freeze-drying; and finally obtaining a composite light evaporator by carbonization treatment.

2. The method for preparing a composite optical evaporator for optical evaporation water desalination according to claim 1, characterized in that: The biogel is made of ice powder seed gel; and the carbon nanotube is made of multi-walled carbon nanotube.

3. The method for preparing a composite optical evaporator for optical evaporation water desalination according to claim 1, characterized in that: The concentration of the carbon nanotubes in the biogel is 12-35 g / L.

4. The method for preparing a composite optical evaporator for optical evaporation water desalination according to claim 1, characterized in that: The mass ratio of copper acetate to biogel in the copper acetate solution is 1:60-125.

5. The method for preparing a composite optical evaporator for optical evaporation water desalination according to claim 1, characterized in that: The preparation method of the ice powder seed glue is as follows: soaking the ice powder seeds in water at a mass ratio of 1:5-10 for 5-20 minutes; and then repeatedly kneading at 2-8°C until the solution becomes colloid and flows slowly, thereby obtaining light yellow transparent paste-like ice powder seed glue.

6. The method for preparing a composite optical evaporator for optical evaporation water desalination according to any one of claims 1 to 5, characterized in that: The following steps are involved: a. Rapidly add carbon nanotubes to the biogel, stir thoroughly to make them evenly dispersed, let it stand and solidify, freeze until the water in the biogel freezes into ice to obtain a hydrogel; freeze-dry the hydrogel to obtain an aerogel base layer; b. Prepare a copper acetate solution and then spray it onto the aerogel substrate. After spraying, freeze-dry it again, then heat it to 500-650°C and carbonize it for 1-2 hours to obtain a composite optical evaporator.

7. The method for preparing a composite optical evaporator for optical evaporation water desalination according to claim 6, characterized in that: The freezing in step a is performed at a temperature below -18°C for 4 to 18 hours; the freeze-drying temperature in step a is -30 to -70°C, and the vacuum degree is not higher than 2Pa.

8. The use of the composite photoevaporator for photoevaporation water desalination according to claim 6, characterized in that: The heating rate in step b is 1-3°C / min.

9. A composite optical evaporator for optical evaporation water desalination prepared by the preparation method according to claim 1, characterized in that: The invention comprises a hydrophilic base layer and a hydrophobic metal surface layer covering the surface of the base layer.

10. The composite optical evaporator for optical evaporation water desalination prepared by the preparation method according to claim 9, characterized in that: Absorbs light of all wavelengths; light absorption rate is not less than 95%.

Citation Information

Patent Citations

  • Copper-containing carbon-based composite efficient photothermal conversion material and preparation method thereof

    CN113023812A

  • Solar evaporator based on biomass hydrogel / nano carbon material and application of solar evaporator

    CN113860413A

  • Biomass-based composite aerogel with nanometal enhanced photothermal effect as well as preparation and application of biomass-based composite aerogel

    CN115594879A

  • Preparation method of moisture-controllable high-salt-tolerance hydrogel interface evaporation fabric

    CN117265874A

  • Coating material and preparation method thereof, heat exchanger and method for treating heat exchanger

    US20220145152A1

Cited By

  • Interface evaporation seawater desalination device based on armor Janus structure and preparation method

    CN120864605A